Peran Pendidikan Tauhid Bagi Anak Sekolah di Era Modernisasi - Asrowi, Asrowi (LPPM STAI La Tansa Mashiro, 2025)
The era of modernization is characterized by rapid technological advancement, open access to information, and swift shifts in social values. Within this context, school-aged children, as the next generation, face major challenges including identity crises, moral degradation, and the influence of secular culture that erodes spiritual values. Tauhid education, as the core of Islamic teachings, plays a central role in shaping children's character and personality based on faith, noble conduct, and social responsibility. This study aims to analyze the extent to which tauhid education contributes to addressing the challenges of modernization and how its implementation strategies are applied in school environments. The method used is a descriptive qualitative approach through literature review and observations in several schools. The findings reveal that effective tauhid education not only teaches the concept of the oneness of God theoretically but also successfully internalizes divine values into the real lives of children through teacher role models, curriculum integration, family involvement, and contextual teaching methods. The main challenges include formalistic approaches, lack of exemplary behavior from educators, educational dualism, and the dominance of secular digital media. Therefore, a synergistic effort among schools, families, and communities is essential in creating an educational atmosphere rooted in tauhid. Comprehensive integration of tauhid education is believed to foster a generation that is spiritually and morally resilient, capable of navigating the complexities of the modern world without losing their Islamic identity.